Income Smoothing and CEO Job Security - Charfeddine, Lanouar (Information Management and Business Review, 2012)
The purpose of this paper is to examine the link between income smoothing and CEO tenure on a sample of 271 U.S companies over the period 1993 to 2003. Moreover, in order to test the extent of income smoothing for job security and specifically for a lengthen tenure; we also have considered some CEOs characteristics such as age and tenure. Empirical results of Wilcoxon statistics and discriminating analysis show that when the current (future) performance is good, the CEOs find the sufficient margins to manage the earnings to leave in reserve for the future performance (or borrow for the current performance). In addition, the results of the multivariate model show that the CEO smooth the income by decreasing accruals, so they shift current earnings to future periods when current earnings is high and future earnings is low to lengthen their tenure.